2017
DOI: 10.1021/acs.cgd.7b00717
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role of Hydrogen Bonding in the Molecular Self-Assembly Process of Sulfamethazine Solvates

Abstract: The new solid forms screening of sulfamethazine was conducted in 16 kinds of different pure solvents. Four new sulfamethazine solvates were reported for the first time, and three crystal structures of solvates were successfully determined from single-crystal X-ray diffraction data. The results showed that sulfamethazine solvate formation directly depended on the solvents used in the experiments. The solvent properties were used to evaluate the effects of solvent on solvate formation. It was found that the H-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…The cyclic assemblies are formed because of the change in shape of the SM molecules, which adopt a propeller shape in lieu of the regularly observed V-shape geometry. 34…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic assemblies are formed because of the change in shape of the SM molecules, which adopt a propeller shape in lieu of the regularly observed V-shape geometry. 34…”
Section: Resultsmentioning
confidence: 99%
“…Associated 2D ngerprint plots were enabled to further quantify the level of contact interactions between the molecules by highlighting their particular close contacts. 51 The HSs maps ( Fig. S3 and S4 †) show the intermolecular contacts as red-colored spots, which indicate the closer contacts of the N-H/O and O-H/O hydrogen bonds.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 97%
“…Moreover, the d norm surface is shown as transparent, which allows the NS group to be visible and highlights the acceptor and donor equally. With respect to NS-MeOH (Figure 8a), the results suggested that the close contacts O7-H7A•••O6 and N3-H3A•••O7 were formed between NS and the methanol molecule, where the deeply red spots on the surfaces indicated the H-bonding contacts [47]. In addition, for further investigation of the interactions among NS and methanol molecules, 2D-fingerprint plots were performed.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%